Increasing Tourists’ Revisit Intention Through Location, Service Quality and Price Perception : Meningkatkan Niat Berkunjung Kembali Wisatawan Melalui Lokasi, Kualitas Layanan dan Persepsi Harga - Wahyudiono, Sulih; Soerjanto, Soerjanto (Institut Pariwisata dan Bisnis Internasional, 2024)
This study aims to examine the impact of location, service quality, and price perception on tourists' revisit intention at Klayar Beach, Pacitan, East Java. A quantitative survey method was employed, involving 350 respondents who had visited Klayar Beach more than once. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression. The analysis revealed that all three variables significantly and positively influenced revisit intention, with service quality being the dominant factor. The findings contribute to the management of natural tourism by providing insights into the factors affecting tourists' revisit intentions. This research is crucial for tourism managers, particularly for Klayar Beach, to formulate effective management and marketing strategies aimed at increasing repeat visits. The novelty of this study lies in its focus on the specific factors influencing revisit intention in a popular natural destination, offering practical recommendations for improving visitor retention and satisfaction.